PEMBELAJARAN KITAB SULLAM MUNAJAH PADA PELAKSANAAN SHALAT SANTRI DI PESANTREN SALAFIYAH RAUDHATUL ATHFAL CIMAHPAR BOGOR - Suwardi; Syamsuddin; Tony Suhartono (PT. IHLAS (Ilmu Adalah Segalanya) - BICARA CENTRE, 2026)
Learning the Sullam Munajah Book is one of the implementations of the study program of Islamic religious sciences based on classical books in Arabic. This study program aims to educate and instill religious values ​​​​in students. Learning the Sullam Munajah book is an example of a study program at the Sullam Munajah Book Boarding School for the implementation of student prayers at the Salafiyah Raudhatul Atfal Cimahpar Bogor Boarding School. This study uses a qualitative approach, and the type of research is descriptive. Data collection techniques use observation, interviews and documentaries. Data analysis uses qualitative descriptive analysis which includes: data reduction, data presentation and drawing conclusions. Data validity uses source triangulation, technique triangulation. Based on the results of the research conducted, it can be concluded that Planning in the process of Learning the Book of Sullam Munajah towards the implementation of students' prayers at the Salafiyah Raudhatul Atfal Cimahpar Bogor Islamic Boarding School is carried out by taking the path of Senior Students' deliberation, by determining learning objectives, learning materials, learning media, learning methods and learning evaluations for the Application of teaching styles about Ubudiyah, especially Prayer which refers to the goals and vision and mission of the boarding school, Implementation in the process of learning the book of Sullam Munajah, can be seen in the senior students who teach are very creative in applying methods and strategies by delivering material using several regional languages ​​​​and lecture methods and practices so that learning is not boring.